Historical gang research methods: an overview - Roth, Mitchel P. (The Oxford handbook of gangs and society, 2024)
This chapter gives an overview of the many historical research methods that have been neglected by gang researchers. Contrary to the longstanding view that historical research is not “scientific,” this chapter demonstrates numerous types of historical research methods, ranging from using archival materials and other primary sources to oral history and newspapers. Often eschewed by social scientists, historical research methods can supplement other research methodologies and lead to a better understanding of gangs at all levels. Historical research is both qualitative and quantitative in scope. Social scientists seem to have neglected this form of research due in no small part to their misunderstanding of what actually constitutes historical data. This chapter will show the myriad forms in which data are available and offer suggestions for incorporating it into their research.